2011
DOI: 10.1007/978-3-642-21631-2_2
|View full text |Cite
|
Sign up to set email alerts
|

The Biology of HDAC in Cancer: The Nuclear and Epigenetic Components

Abstract: Traditionally, cancer has been regarded to originate from genetic alterations such as mutations, deletions, rearrangements as well as gene amplifications, leading to abnormal expression of tumor suppressor genes and oncogenes. An increasing body of evidence indicates that in addition to changes in DNA sequence, epigenetic alterations contribute to cancer initiation and progression. In contrast to genetic mutations, epigenetic changes are reversible and therefore an attractive target for cancer therapy. Many ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 134 publications
1
86
0
Order By: Relevance
“…Currently, the efficacy of 420 different HDAC inhibitors tested in the clinic has been largely restricted to haematological malignancies. Whereas the effect of HDAC inhibitors used in the treatment of solid tumours are disappointing 43,44 , it has also been shown that HDAC inhibitors can induce EMT in prostate cancer cells 45 . HDAC1 and HDAC2 have been reportedly shown to function as tumour suppressors in epidermis and lymphomas [46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the efficacy of 420 different HDAC inhibitors tested in the clinic has been largely restricted to haematological malignancies. Whereas the effect of HDAC inhibitors used in the treatment of solid tumours are disappointing 43,44 , it has also been shown that HDAC inhibitors can induce EMT in prostate cancer cells 45 . HDAC1 and HDAC2 have been reportedly shown to function as tumour suppressors in epidermis and lymphomas [46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
“…52,53 During the last decade, many drugs with histone deacetylase (HDAC)-inhibiting action have been shown to induce growth arrest, apoptosis, and differentiation of tumor cells. 54,55 It was recently shown that different types of lesions vary in the expression of HDACs 56,57 and that tissues (lesions and endometrium) from patients have different levels of H3K9 and H4K16 acetylation compared to control tissues. 58,59 Thus, evidence has started to accumulate that endometriotic lesions have a characteristic histone code and that global H3 and H4 acetylation within promoter regions of candidate genes is differentially modulated in lesions.…”
Section: Recommendation (New)mentioning
confidence: 99%
“…There are currently more than 80 clinical trials underway to determine the therapeutic efficacies of several HDAC inhibitors that have shown anti-neoplastic functions in cell culture and animal studies. Two HDAC inhibitors, Vorinostat and Romidepsin, have been approved for use in treatment of cutaneous T-cell lymphoma (5,6). Other HDAC inhibitors have been used successfully as mood stabilizers and anti-epileptics and have shown promise in treatment of diverse neurological diseases such as Huntington and Alzheimer disease, amyotrophic lateral sclerosis, and spinal muscular atrophy (7,8).…”
Section: Hdacsmentioning
confidence: 99%